Challenges and Strategies in Nigeria’s Fight Against Corruption: The Role of Public Administration and Anti-Corruption Agencies - Okolie, Ugo Chuks; Egbon, Thomastina Nkechi (PERSPEKTIF, 2025)
This study examined the role of public administration in combating corruption in Nigeria, emphasizing the contributions of anti-corruption agencies. Adopting a historical study approach, the study traced the development and influence of key agencies, including the Economic and Financial Crimes Commission (EFCC) and the Independent Corrupt Practices and Other Related Offences Commission (ICPC). The Institutional Theory was used to analyze the relationship between administrative frameworks and anti-corruption efforts. The study provides unique insights into the effectiveness of anti-corruption agencies, highlighting their achievements and the constraints they face, including limited resources and political challenges. The findings indicated that although these agencies have achieved significant progress, they face challenges such as political interference, insufficient institutional capacity, and poor coordination, which limit their effectiveness. The study concluded that public administration is essential in this fight, but more extensive reforms are necessary to enhance the strength and independence of these agencies. The study recommended the creation of an independent body to oversee the performance of anti-corruption agencies and ensure improved accountability in their operations. The study's practical contribution is found in its policy suggestions for enhancing anti-corruption frameworks. In contrast, its theoretical contribution adds depth to the discussion on institutional integrity and governance in societies prone to corruption.